Diagnostic utility of IL-18 plasma levels in distinguishing abdominal from non-abdominal sepsis - Anna Herminghaus; Mykola Totskyi; Christian Vollmer; Thomas Dimski; Timo Brandenburger; Timo Brandenburger; Anne Kuebart; Helen Rinderknecht; Christian B. Bergmann; Ina Vernikouskaya; Jasmin Maria Bülow; Nils Becker; et al. (Frontiers in Immunology)
BackgroundAbdominal sepsis is a critical and high-risk condition in intensive care, characterized by diagnostic challenges, complex treatment, and high mortality. Non-specific symptoms and the difficulty of discriminating harmful bacteria from the normal flora complicate a timely diagnosis and treatment. Although timely interventions are crucial, the best timing of surgery remains uncertain, especially in unstable patients. Diagnostic markers like C-reactive protein, procalcitonin, and interleukins help guide diagnosis but often lack specificity of an abdominal focus. This study aims to identify possible additional markers for earlier detection of abdominal sepsis.MethodsPlasma samples were collected from 47 sepsis patients at the day of sepsis diagnosis, and from 10 healthy controls. Patients were retrospectively categorized into those with abdominal (n=23) and those with non-abdominal (n=24) sepsis. Patient`s characteristics, clinical outcomes, physiological and laboratory parameters, and cytokine levels were assessed. Receiver operating characteristic curves and Spearman correlation analyses were conducted.ResultsAge and sex proportions were comparable across the sepsis groups, as were the chronic disease prevalence, the severity of illness and mortality rates. Patients with abdominal sepsis were more likely to undergo emergency surgeries. Pro-inflammatory cytokines like IL-6, MCP-1, and IL-18 were elevated, as was the anti-inflammatory IL-10 in both sepsis cohorts compared to healthy controls. IL-18 was particularly associated with a more severe inflammatory response in non-abdominal sepsis. IL-18 levels below 1892.00 pg/mL showed 82.6% sensitivity and 56.5% specificity for identifying patients with abdominal sepsis, with a significant diagnostic accuracy (AUC 0.68, p = 0.034). This suggests IL-18 as a useful additional moderate predictor for critical cases.ConclusionThe results demonstrate that IL-18, IL-6, MCP-1, and IL-10 are increased in sepsis, while IL-18 may serve as an additional biomarker for distinguishing abdominal from non-abdominal sepsis.